Elevated Risk of Cancer After Solid Organ Transplant in Childhood: A Population-based Cohort Study. Issue 3 (March 2019) - Kitchlu, Abhijat; Dixon, Stephanie; Dirk, Jade S.; Chanchlani, Rahul; Vasilevska-Ristovska, Jovanka; Borges, Karlota; Dipchand, Anne I.; Ng, Vicky L.; Hebert, Diane; Solomon, Melinda; Michael Paterson, J.; Gupta, Sumit; et al.
Abstract : Background: Cancer risk is elevated among adult transplant recipients, but there is limited data regarding long-term cancer risk and mortality in pediatric recipients. Methods: We conducted a population-based retrospective cohort study in Ontario, Canada. We included pediatric recipients of solid organ transplants at the Hospital for Sick Children, Toronto, from 1991 to 2014, and compared rates of new cancers and cancer-specific mortality to nontransplanted Ontario children born in the same year. We constructed standard and time-dependent Cox proportional hazards models accounting for competing risk of death. Results: A total of 951 recipients (kidney, n = 400; liver, n = 283; heart, n = 218; lung, n = 36; multiorgan/small bowel, n = 14) were compared with 5.3 million general population children. Mean (SD) age was 8.2 (6.4) years; 50% were male. Over a mean (SD) follow-up of 10.8 (7.1) years, cumulative incidence of cancer was 20% in recipients and 1.2% in the general population (incidence rate ratio, 32.9; 95% confidence interval [CI], 26.6–40.8). Risk was highest in the first year posttransplant (adjusted hazard ratio [aHR], 176; 95% CI, 117–264), but remained elevated beyond 10 years (aHR, 10.8; 95% CI, 6.3–18.6). Lymphoproliferative disorders were predominant (77%); however, solid cancers (renal, sarcomas, genital, thyroid) were seen. Recipients of lung or multiorgan transplants were at highest risk. Cancer-specific mortality was also higher among recipients (HR, 93.1; 95% CI, 59.6–145.2). Conclusions: Childhood transplant recipients have a 30 times greater cancer incidence versus the general population. Further investigation is needed to guide screening strategies in this at-risk population. Abstract : Supplemental Digital Content is available in the text.